Exploring the Use of Mobile Instant Messaging Among Middle-aged Adults in Social Relationships Maintenance with Family and Friends - Olivine Wai-yu Lo (Department of Communications, Universitas Islam Indonesia, 2020)
Smartphone has played a vital role in shaping our modern daily life, including gratifying our needs in entertainment, information search, and social networking. Nowadays, mobile instant messaging (MIM) has been adopted as a main communication tool not only by the younger generations, but also by the older groups. However, most studies have focused on how the young users communicate with their peers, while the middle-aged group has not received any proper attention from researchers. This study aims to examine middle-aged adults’ (40 to 60 years old) use of MIM as a complementing tool of the traditional communication forms to sustain relational involvements with their friends and family members. Applying a snowballing online survey method, this study has asked a group of students of a communication research class of a mid-size private university in Hong Kong to deliver the online questionnaire to their parents, also asked their parents to send the questionnaire to their middle-aged friends who have children. This study finds two major types of MIM functions being used: visual-based and audio-based. These functions are significantly related to three newly found relational gratifications: friendship maintenance, family relations maintenance, and troubleshooting. This study expands the understanding of specific MIM communication patterns among the respondents, also explores the age and gender differences in MIM communication. Keywords: Mobile instant messaging, relational maintenance gratifications, family relations, middle-aged adults.